The efficacy of Emla® and 5% lignocaine gel for anaesthesia of human gingival mucosa - A. S. McMillan, *D. Walshaw, J. G. Meechan (Blackwell Synergy, 2000)
A topical anaesthetic made up of 2.5% lignocaine and 2.5% prilocaine in a eutectic mixture (Emla, Astra Pharmaceuticals, Kings Langley, UK) has been used as an oral analgesic during clinical procedures such as maxillary and mandibular arch bar removal,1 and gingival probing and scaling.